KEMANDIRIAN KEUANGAN DAERAH: KEBIJAKAN DESENTRALISASI FISKAL DAN OTONOMI DAERAH DI INDONESIA: regional needs and choices, provision of public services, additional tax costs, budget money - Astuty, Pudji (JAMAK, 2018)
Tax decentralization is one of the main components of decentralization. In order for the government to be able to be used effectively, and given the freedom to provide the results of service provision in the public sector, they must be supported by adequate financial resources originating from Regional Original Income (PAD) including tax fees, tax and non-tax revenue sharing, loans, and subsidies from the Central Government. Implementation of fiscal decentralization is expected to improve public values and encourage economic growth so that it will have an impact on the community level. However, that won't work if some success cannot be ignored